Durable left ventricular assist device implantation in extremely obese heart failure patients. Issue 3 (3rd January 2019) - Lee, Andy Y.; Tecson, Kristen M.; Lima, Brian; Shaikh, Asad F.; Collier, Justin; Still, Sasha; Baxter, Ronald; DiMaio, John M.; Felius, Joost; Carey, Sandra A.; Gonzalez‐Stawinski, Gonzalo V.; Nauret, Richard; et al.
Abstract: Left ventricular assist devices (LVADs) have improved clinical outcomes and quality of life for those with end‐stage heart failure. However, the costs and risks associated with these devices necessitate appropriate patient selection. LVAD candidates are becoming increasingly more obese and there are conflicting reports regarding obesity's effect on outcomes. Hence, we sought to evaluate the impact of extreme obesity on clinical outcomes after LVAD placement. Consecutive LVAD implantation patients at our center from June 2008 to May 2016 were studied retrospectively. We compared patients with a body mass index (BMI) ≥40 kg/m 2 (extremely obese) to those with BMI < 40 kg/m 2 with respect to patient characteristics and surgical outcomes, including survival. 252 patients were included in this analysis, 30 (11.9%) of whom met the definition of extreme obesity. We found that patients with extreme obesity were significantly younger (47[33, 57] vs. 60[52, 67] years, P  < 0.001) with fewer prior sternotomies (16.7% vs. 36.0%, P  = 0.04). They had higher rates of pump thrombosis (30% vs. 9.0%, P  = 0.003) and stage 2/3 acute kidney injury (46.7% vs. 27.0%, P  = 0.003), but there were no differences in 30‐day or 1‐year survival, even after adjusting for age and clinical factors. Extreme obesity does not appear to place LVAD implantation patients at a higher risk for mortality compared to those who are not extremely obese; however, extreme obesity was associated with an increased risk of pump thrombosis, suggesting that these patients may require additional care to reduce the need for urgent device exchange.